HUBUNGAN PERMAINAN BALOK DENGAN PERKEMBANGAN MOTORIK HALUS ANAK USIA 3-4 TAHUN DI KELOMPOK BERMAIN TARBIYATUL ATFAL GRESIK - Khalimatus Sa?diya, Lida; Mu?afifah, Siti (JURNAL KEPERAWATAN SEHAT, 2015)
Play block of flats is one of the tools of play construction which is beneficial for the child. Not only to aspects of cognitive, motor, but also to improve the childs emotional intelligence (EQ). This time the fine motor development is the ability associated with the physical skills involving the coordination of smooth muscles/small. The purpose of the research is to know the relationship game fine motor development with beams between the ages of 3-4 years at Playgroup tarbiyatul Atfal of Gresik Regency. Analytical research by design correlation using the approach of cross sectional. The population of the entire child playgroup age 3-4 years by as much as 30 respondents, sampling the sampling, using a total of 30 sample respondents. Taken using a sheet of observation and KPSP sheet. After the accumulated data processing is carried out and continued with the statistical test cross tabs. Children are expected to enhance their learning at home not only in school, this beam is easy game played by children and play the game these beams depends on the childs condition as well as the physical conditions, children, the environment, the elderly and childrens own interests. Thats the role of the parents is still important to reach the stage of child development, such as helping children to play or increase other motor motion, children could play well and the development of motoric in accordance with the stage of development is expected to in the future.Key words : fine motor, block game, kids playgroup